Hubungan antara Pola Makan dan Aktifitas Fisik dengan Kadar Gula Darah pada Penderita Diabetes Melitus Tipe II di Puskesmas Hanura Kabupaten Pesawaran Tahun 2025 - Junisa Herawati; Farhan Al Farisi; Dian Arif Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2026)
Type 2 Diabetes Mellitus is a chronic metabolic disease with a continuously increasing prevalence. In Indonesia, the number of patients is projected to reach 28.57 million by 2045, rising from 19.47 million in 2021, with 236,711 deaths reported in 2021. In Lampung Province, 89,981 cases were recorded, while Pesawaran Regency reported 1,826 hospitalized cases in 2023. Diabetes leads to serious complications due to uncontrolled blood glucose levels, primarily triggered by unhealthy dietary patterns and low physical activity. Control efforts include health education, the Prolanis program, and the promotion of regular physical activity. This study aimed to analyze the relationship between dietary patterns and physical activity with blood glucose levels among patients with type 2 diabetes at Hanura Public Health Center in 2025. This study employed a quantitative cross-sectional design with total sampling of 32 respondents with type 2 diabetes. Data were collected using a dietary pattern questionnaire, the International Physical Activity Questionnaire (IPAQ) for physical activity assessment, and a glucometer for blood glucose measurement. Data analysis was conducted using the Chi-Square test. Univariate analysis showed that most respondents had an adequate dietary pattern (59.4%; 19 participants), moderate physical activity levels (43.8%; 14 participants). normal blood glucose levels (50.0%; 16 participants). Bivariate analysis revealed a significant relationship between dietary patterns, physical activity, and blood glucose levels (p < 0.001). Conclusion: Irregular dietary habits and low physical activity contribute to increased blood glucose levels. Patients with diabetes are advised to follow the 3J dietary principle (Schedule, Amount, Type) and engage in regular physical activity for at least 150 minutes per week.